Appointment of a Qualified Non-Catholic as Defender of the Bond: Canon 1435 - Wellspring, Julian B. (CLSA advisory opinions, 2001-2005, 2001)
Several years ago now Diocese X employed a non-Catholic person to work in a secretarial capacity in its tribunal office. Over time she became the senior secretarial assistant in the office and therefore very familiar with the processing of cases. Her interest in the work has developed to the point where she wants to become professionally qualified and exercise the office of defender of the bond. If she became professionally qualified, could she be appointed defender of the bond?